High-dynamic compressive and tensile strength of specimens made of cementitious materials. (March 2020) - Binder, E.; Reihsner, R.; Yuan, Y.; Mang, H.A.; Pichler, B.L.A.
Abstract: The strength of specimens made of cementitious materials increases with increasing loading rate. Herein, the model of Fischer et al. (CCR 58, 2014, 186–200) is revisited in the context of high-dynamic compression and extended to high-dynamic tension. The model is based on the assumptions (i) that cracking will start if the quasi-static material strength is reached, and (ii) that the high-dynamic strength gain refers to the increase of the stress during the failure process of the tested specimen. The model explains the behavior of cylindrical specimens made of dry cement paste, mortar, and concrete, subjected to high-dynamic compression. It also elucidates the performance of cylindrical specimens made of dry mortar and concrete, subjected to high-dynamic tension. It is concluded that the high-dynamic strength gain is a structural effect and that structures will be damaged if the dynamic stress exceeds the quasi-static strength, no matter how fast the stress is increased and how short the stress pulse lasts.